Digital fabrication of colors with colloidal crystals and colloidal glasses - Rahul Karyappa; Deepshikha Arora; Tzee Luai Meng; Qiang Zhu; Joel Yang; Hongfei Liu (Next Nanotechnology)
The structural color properties of colloidal arrays can be controlled by colloidal assembly via tuning the size, composition, and ordering of colloidal particles and their formation at the macroscale. Controlled assembly and patterning offer many advantages for the technological development of photovoltaics, optics, and lab-on-a-chip, where the ordering of particles can influence the properties and functions of a system. Many techniques have been well established for patterning ordered colloidal arrays (colloidal crystals), and disordered colloidal arrays (colloidal glasses). However, they are time-consuming and require additional steps such as masking, etching, or stamping. The advent of digital manufacturing, in which additive manufacturing is combined with computer-aided design (CAD), can overcome some of the challenges in fabricating structures from colloidal particles. This article presents a review of recent strategies for digitally fabricating 1D (e.g., single line), 2D (e.g., arrays of dots and patterns with lines), and 3D (e.g., dots and balls) colloidal crystals and glasses, including inkjet printing, direct ink writing, electrohydrodynamic jet printing, two-photon lithography, and digital light processing. The requirements of colloidal ink formulations for different 3D printing methods are discussed. The effects of the wettability of the printed ink on the ordering of colloidal particles in the fabricated structures and the resulting structural colors are discussed. Finally, a summary and perspective on future development are presented.